Lateral Thoughts : Behind the scenes at the printer. (14th October 2019) - Gardner, Kate
Abstract: In the small country town of Bourne, Lincolnshire, just a minute's walk from the high street, a steady stream of people are entering and leaving an attractive redbrick building that was originally a malthouse. It's shift change at Warners Printers, which has printed every issue of Physics World for the past 31 years.